Modelling household behavioural changes as an opportunity for sustainable home energy - Zainudin, Norzalina; Lau, Jasmine Leby; Munusami, Chandramalar (Springer, 2021)
This paper aims to employ behaviour change theories in predicting consumers’ intention of buying energy-efficient products. A stratified sampling of 500 face-to-face interview questionnaires was used in two regions of Peninsular Malaysia. The findings from the evaluation of absolute indices of the structural model showed that the criterion of the model is good-of-fit with values greater than 0.9. Besides, the analysis of the direct effect model also found that consumers’ intention to buy energy-efficient products is influenced by perceived product values. As for the indirect model, attitude determines the relationship between consumers’ perceived product value, subjective norm, responsibility and intention to buy energy-efficient products. A consumer’s perception of product values and attitude is crucial for consumers to form a more favourable mindset towards these green innovation products. In addition, the communication initiatives that develop consumers’ trust about the benefits of the products are some of the various ways to encourage consumers’ purchasing behaviour. Hence, this study attempts to provide a valuable insight into Malaysian consumers’ behaviour regarding energy-efficient products. Furthermore, this study extends an application of the behavioural theories by examining variables in a composite model. The findings of the study suggest that policy makers should thoroughly set the interventions to harmonise the traditional approach using rebates and subsidised incentives since behavioural interventions are considered to be valuable complements when they are jointly implemented.